Analisis Kemampuan Pemahaman Konsep Matematika Siswa Kelas X SMK ASISI Jakarta Pada Materi Logaritma - Kristituta Alma Tri Ananda; Margaretha Silvia; Anjela Safira; Widhi Kasih Mulya Juliani (Universitas Maritim AMNI Semarang, 2023)
This study aims to describe the level of mathematical concept understanding ability of class X students of SMK Swasta Asisi Jakarta on logarithm material. The research method used by the research is descriptive qualitative method. The research subjects were 13 students of class X AKL SMA ASISI Jakarta and one class X mathematics teacher. Data collection was carried out through a description test related to logarithm material which refers to 3 indicators of concept understanding, namely linking various concepts, presenting concepts in the form of mathematical representations, and using appropriate concepts in solving problems. The results showed that students' ability to understand mathematical concepts was still relatively low with the acquisition of average percentage data of 33.33%. Students still have difficulty in linking concepts, presenting concepts in mathematical representations, and applying logarithm concepts to solve problems. The ability to understand mathematical concepts of class X students of SMK Swasta Asisi Jakarta on logarithm material is still relatively low. This study concludes that there is a need to improve students' understanding of mathematical concepts, especially in logarithm material so that students are able to determine and apply the right concepts in solving mathematical problems.